2022
DOI: 10.1093/jamiaopen/ooab116
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal telemedicine during COVID-19: patterns of use and barriers to access

Abstract: Lay Summary To protect pregnant patients from infection during the COVID pandemic, maternity care providers turned to video and phone visits (“telemedicine”) to provide as much prenatal care as possible. To evaluate this change in our prenatal care program, we surveyed 164 pregnant people who had participated in a virtual prenatal visit about their care. Participants reported both positive and negative experiences, ranging from appreciation for having a safer option than in-person visits duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 20 publications
1
15
0
4
Order By: Relevance
“…Previous studies conducted prior to the pandemic as well as during the pandemic has demonstrated the significance of telemedicine prenatal care [ 121 , 122 ]. However, others have raised concerns regarding equity in access to care, particularly in resource-limited settings [ 123 ]. The 6-telehealth technology-enable interventions identified in this scoping review focused on exercise, selfcare, prenatal counseling and behavioral health.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies conducted prior to the pandemic as well as during the pandemic has demonstrated the significance of telemedicine prenatal care [ 121 , 122 ]. However, others have raised concerns regarding equity in access to care, particularly in resource-limited settings [ 123 ]. The 6-telehealth technology-enable interventions identified in this scoping review focused on exercise, selfcare, prenatal counseling and behavioral health.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps, women of color are satisfied with telehealth when they have access to it, but securing that access may be a greater challenge. For example, a recent survey of pregnant women living in rural areas found that although women reported a positive experience with prenatal telehealth visits overall, common barriers included poor internet and phone connectivity, childcare responsibilities, and lack of equipment [ 21 ], factors that may disproportionately impact minority groups. Although it is important to understand women’s experiences using telehealth, ensuring equitable access to these services is paramount and public health programs or policies are needed to reduce barriers to telehealth access.…”
Section: Discussionmentioning
confidence: 99%
“…A respeito dos resultados da teleassistência, a maioria dos artigos relatou que os pacientes sentiram-se satisfeitos; incluindo gestantes de alto risco (JENAGATHAN et al, 2020). Essa satisfação foi relacionada à facilidade da consulta, segurança e diminuição de barreiras como o transporte e o risco de infecção para poder ter acesso ao cuidado (JENAGATHAN et al, 2020, MORGAN et al, 2022, FARRELL et al, 2022, CHEN et al, 2020. Também foi descrita a eficácia da telessaúde na prevenção de desfechos materno-fetais negativos, como restrição do crescimento fetal, diabetes gestacional e pré-eclâmpsia (PALMER et al, 2021), depressão perinatal (LATENDRESSE et al, 2021); GAO et al, (2022) inclusive revelaram que os resultados obstétricos não tiveram diferenças significativas entre os pré-natais realizados de forma presencial e remota.…”
Section: Introductionunclassified
“…Também foi descrita a eficácia da telessaúde na prevenção de desfechos materno-fetais negativos, como restrição do crescimento fetal, diabetes gestacional e pré-eclâmpsia (PALMER et al, 2021), depressão perinatal (LATENDRESSE et al, 2021); GAO et al, (2022) inclusive revelaram que os resultados obstétricos não tiveram diferenças significativas entre os pré-natais realizados de forma presencial e remota. As dificuldades relatadas foram principalmente devidas a dificuldades de acesso (MADDEN et al, 2020;FARRELL et al, 2022) e a uma relativa insegurança entre as gestantes comparado ao modelo presencial (MORGAN et al, 2022).…”
Section: Introductionunclassified
See 1 more Smart Citation